An application of particle swarm optimisation method for solving network reconfiguration problem in distribution system. Issue 2 (2016) - Srivastava, Ishan; Arya, Anoop
Particle swarm optimisation (PSO) is an intelligent optimisation algorithm with different variants that are developed according to the targeted application. These variants are obtained by changing the parameters of the PSO algorithm like inertia weight, constriction factor, and acceleration factor. These variants can be utilised for various power system optimisation requirements such as distribution automation, for a targeted application. Distribution network reconfiguration (DNR) is one such application that involves high computational complexity and requires an intelligent optimisation technique for its solution. In this paper different variants of PSO are applied to DNR problem like binary PSO, crazy PSO, and enhanced inter coded PSO for 16 bus and 33 bus test systems. These variants ensure proper exploration and exploitation of the search space to obtain optimum and quick solution for the DNR problem.